Rapid hydrodehalogenation of chlorinated benzoic acids using mechano-thermally prepared Raney alloy with enhanced kinetics. Issue 4 (August 2021) - Hegedüs, Michal; Gáborová, Katarína; Weidlich, Tomáš; Kalivoda, Pavel; Briančin, Jaroslav; Tóthová, Erika
Abstract: The present study reports on the degradation of chlorinated benzoic acids (CBAs), commonly present in the environment as pollutants, by a hydrodehalogenation reaction utilizing the Raney Al-Ni alloy (50:50 wt% Al:Ni). The hydrodehalogenation reaction using the Raney Al-Ni alloy has already been proven as an efficient tool for fast and efficient degradation of halogenated persistent organic pollutants (POPs). Herein, the nano-structured Raney Al-Ni alloy was prepared by an alternative mechano-thermal approach starting from pure elements in a form of powders. The prepared alloy was characterized by X-ray diffractometry, scanning electron microscopy, particle size distribution, and active surface area analyses. The properties of the material were compared with a commercial sample of the same alloy prepared by the atomization process. The activity of the synthesized alloy was evaluated as removal efficiency and a rate of dehalogenation of three different CBAs – 2-chlorobenzoic acid, 2, 6-dichlorobenzoic acid, and 2, 3, 6-trichlorobenzoic acid ( trysben ); used in the past as an herbicide. Dehalogenation of all three tested CBAs yielded benzoic acid as the only product and followed the first-order reaction kinetics. Compared to the commercially available alloy, enhanced kinetics of CBAs removal was achieved, owing to the solid-state properties of the mechano-thermally prepared alloy. Graphical Abstract: ga1 Highlights: Nano-structured Raney Al-Ni alloy (50:50 wt% Al-Ni) can be prepared via green combined mechano-thermal approach. Prepared alloy can effectively and rapidly remove chlorinated benzoic acids considered as environmental pollutants with long half-lives in soils and groundwaters. Proposed hydrodehalogenation approach could be used for highly contaminated wastewaters containing chlorinated organics parameter.